Interactive Augmentation of Learning Environment for International Students - Elena A. Pavlichenko, Polina G. Berdnik, Liudmyla A. Petrova, Yurii S. Dolhyi, Aleksei V. Petrov, (Opción, 2019)
This article analyzes approaches towards technology design aimed at creating an interactive learning environment for international students taking the pre-university courses in the higher educational establishment. The methodological basis of research involves provisions of dialectical materialism about the theory of knowledge and methodological conceptions of personality formation in education. Research results indicate that primary equal control and test groups took different paths and reached different points by the end of the course. As a conclusion, the found solution of a learning environment allows us to shape and put a new vision of teaching and learning into the common system design.